Labor market issues in China - Giulietti, Corrado; Tatsiramos, Konstantinos; Zimmermann, Klaus F. (Research in labor economics ;, 2013)
After three decades of economic reform, China is experiencing substantial demographic changes and a steady structural transformation toward a market economy. These phenomena pose major challenges for the Chinese labor market, which are at the center of the booming academic and policy research in recent years. This volume presents fresh knowledge on labor market issues in China. It contains eight original research articles which offer insights and answers to question such as: Which are the most important challenges of the Chinese labor market? How does rural-urban migration affect occupational choice in rural China? Does urban occupational mobility differ across gender? Which is the cost of job displacement in urban labor markets? Is over-qualification affecting the hiring probability across educational groups? How does the social insurance system perform in terms of coverage of urban workers? Which are the incentive problems in the new rural pension program?